Design of a homogeneous radiation field in an LED photo-reactor. Issue 4 (December 2014) - Yu, Linlong; Achari, Gopal; Langford, Cooper H.
Abstract : In this paper, a radiation field model for a light-emitting diode-based photocatalytic reactor has been developed. The model was tested using experimental data, and good agreement between the model and experimental results was noted. The model was used to investigate the impact of irradiated distance on the homogeneity of radiation field because it is shown that a homogeneous radiation field is the most efficient. The model can be used to design an efficient photoreactor by selecting the optimal gap between adjacent light-emitting diodes, the irradiated distance and the light output of light-emitting diodes.